Membrane dynamics shape TCR-generated signaling - He, Hai-Tao; Bongrand, Pierre (Frontiers in Immunology, 2012)
Despite intensive investigation, the mechanisms of TCR-mediated signal generation remain poorly understood. Here we review various dynamic processes at the cell membrane that might critically control this signaling. Firstly, we summarize recent reports providing new information on the sensitivity of TCR-ligand interaction to the membrane environment and particularly to applied forces. Secondly, we review recent evidence that forces and displacements are continuously generated at cell surfaces. Thirdly, we summarize recent experimental evidence demonstrating the capacity of forces to generate signals. Lastly, we provide a quantitative model to exemplify the capacity of dynamic processes to modulate TCR properties such as specificity that were previously difficult to explain with conventional models. It is concluded that the described dynamic processes must be integrated into current models of TCR signaling.